Development of APLAR-COPCORD Core Questionnaire for Identification of Risk Factors for Non Specific Low Back Pain - Siddiqui, M Nure Alom; Islam, M Nazrul; Haq, Syed Atiqul; Sultana, Shahnaj; Rhman, MK; Khan, MMR (TAJ: Journal of Teachers Association, 2018)
Background: Non specific low back pain (NSLBP) has been identified as one of the commonest rheumatic disorders in prevalence surveys in Asia-Pacific Objective: Development of a core questionnaire for identification of risk factors of NSLBP at community level. Methods: Following steps were followed: 1) item generation from literature survey, existing Nordic questionnaires and patient focus group discussions, 2) development of a preliminary APLAR-COPCORD English questionnaire, 3) translation into target language, back translation and development of a synthetic target language version, 4) adaptation of the synthetic target language version through tests of comprehensibility, content validity test-retest reliability, and 5) finalization of the English questionnaire. . Results: 45 items were generated. A preliminary English questionnaire was developed. Conclusion: The developed English questionnaire will serve as an efficient tool for identification of risk factors of NSLBP in Asia-Pacific communities. TAJ 2011; 24(2): 85-90